Enhancing pediatric airway safety using the electronic medical record. (8th September 2018) - Rameau, Anaïs; Wang, Ellen; Saraswathula, Anirudh; Pageler, Natalie; Perales, Shanna; Sidell, Douglas R.
Abstract : Objective: Difficult intubations are not uncommon in tertiary care children's hospitals, and effective documentation of the difficult airway is a fundamental element of safe airway management. The primary goal of our quality improvement initiative was to improve access to airway information via an alert and documentation system within the electronic medical record (EMR). Methods: We created a difficult airway alert within the EMR, linking common airway evaluation templates used by specialists involved in airway management. We assessed the time required for different specialists to answer an airway information questionnaire using the electronic charts of patients before and after the EMR modification. Satisfaction with the EMR modification was also surveyed. Results: Questionnaires were administered to 12 participants before the Epic (Epic Systems Corp., Verona, WI) changes were implemented and to 19 participants after they were implemented. Each participant was asked to answer the airway data questionnaire for two patients, for a total of 24 questionnaires before the EMR changes and 38 questionnaires after the changes. Respondents averaged 7.24 minutes to complete the entire airway data questionnaire before the EMR changes and 3.16 minutes following modification ( P < 0.0001). Correct airway information was more consistently collected with the modified EMR (98.6% vs 51.4%, P < 0.00001). Satisfaction surveys revealed that participants found the accessibility of airway data to be significantly improved following the EMR changes. Conclusion: An EMR airway alert that provides rapid access to relevant airway information critical tool during urgent and emergent events. Based on our preliminary data, further use of this instrument is expected to continue to improve patient safety and practitioner satisfaction. Level of Evidence: 4 Laryngoscope, 128:2885–2892, 2018